Wear resistant epoxy composites with diisocyanate-based self-healing functionality - Khun, Nay Win (2016)
Hexamethylene diisocyanate (HDI) filled microcapsules were developed and incorporated in epoxy matrices to form a new type of wear resistant epoxy composites. The tribological properties of the epoxy composites were systemically investigated. The friction and wear of the composites slid against a Cr6 steel ball at different sliding speeds under various normal loads decreased with increased microcapsule content because of the lubricating effect of released HDI liquid from ruptured microcapsules during the wear test and the self-healing process of the released HDI liquid with the moisture to form new polyurea layers on the wear track. It can be concluded that the incorporation of microencapsulated HDI liquid is an effective way to lessen the wear of the epoxy composites during sliding via the self-healing process with a concurrent self-lubricating effect of the released HDI liquid.